The Characteristics Of Arabic Language Textbooks Of Madrasah Ibtidaiyah - Machmudah, Umi; Khuzaimah, Khuzaimah; Sholihah, Mufidatus (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research aims to describe the various main angles that become potential which include: 1) Principles for preparing teaching materials, 2) Organization of teaching materials, 3) Language skills 4) Learning objectives and 5) Types of evaluations, which are applied in Arabic textbooks of Madrasah Ibtidaiyah in Malang. This research can be categorized as descriptive research. The content analysis research strategy is seen as the right strategy to draw the valid conclusions from a book or document. The results of the research are: 1) The principles of teaching materials applied in the preparation of the books: valid, meaningful, tendency and concern, worthy to be studied and having global principles. 2) The organization of teaching materials applied in the preparation of the books is a logical and psychological organization. 3) The language skills and aspects applied in the preparation of the books are mufrodat, istima ', kalam, qiro'ah, and kitabah. 4) The learning objectives formulated in the books are students' abilities in identifying hijaiyah letter sounds on the material presented, discovering the meaning of oral or written discourse, and being able to have dialogue in Arabic language, and 5) The types of evaluations that are applied in the books are: a) making questions based on the available answers, b) answering questions by choosing the correct answer, c) interpreting mufrodat, d) writing sentences and their meanings, e) composing words to be a perfect sentence, f) translating Indonesian sentences into Arabic, g) translating from Arabic into Indonesian, h) completing empty sentences to be perfect sentences, i) writing Arabic numbers, j) connecting mufrodat which has opposite meaning, and k) give harokat to a word.